Preying frequency of white-throated kingfisher, Halcyon smyrnensis (Linnaeus, 1758) - Naher, Habibon; Sarker, Noor Jahan (Ecoprint: An International Journal of Ecology, 2016)
A study was conducted on ‘Preying frequency of White-throated Kingfisher, Halcyon smyrnensis (Linnaeus 1758) in Bangladesh’ from September 2008 to September 2011 at Nikunja-1 in Dhaka City Corporation area. The objectives of the study were to know the average preying frequency per day in different months and seasons. Scan sampling method was followed to study the kingfishers’ behaviour. At regular interval (5 minutes), day long observation was made with some observatory equipments. It preyed 4.1± 2.3 times per day on an average. They had bimodal feeding patterns, at morning (0701-1200 h) and afternoon (1401-1800 h). At noon they avoided preying. December was the highest preying month and summer was the highest unsuccessful preying season in the year. The food items composed of 36.6% arthropods and 61.1% fishes. Arthropods were preyed for 1.5 times and fishes for 2.5 times on an average per day. In association with arthropods and fishes they also preyed on amphibians and reptiles occasionally. Arthropods were preferred highly during non breeding season but fishes were preferred in breeding season for saving time and energy.ECOPRINT 22: 39-49, 2015